Loop9 closure technique for mucosal defects after colorectal endoscopic submucosal dissection (with video) - Tanabe, Mayo; Inoue, Haruhiro; Shimamura, Yuto; Toshimori, Akiko; Navarro, Marc Julius Hernandez; Fujiyoshi, Yusuke; Fujiyoshi, Mary Raina Angeli; Shiomi, Daijiro; Kishi, Yumi; Ushikubo, Kei; Nishikawa, Yohei; Onimaru, Manabu; Ito, Takayoshi; Uragami, Naoyuki; Yokoyama, Noboru (Endoscopy International Open, 2024)
Background and study aims Mucosal defect closure after colorectal endoscopic submucosal dissection (ESD) has the potential to reduce the occurrence of delayed adverse events (AEs) such as bleeding and perforation. This study aimed to assess the feasibility and effectiveness of the Loop9 method for closing mucosal defects following colorectal ESD.Patients and methods A retrospective single-center study was conducted using prospectively collected data from May 2020 to March 2023. Loop9 was deployed through a single instrument channel and anchored with clips at the defect site. Closure was accomplished by tightening the loop and deploying additional conventional clips as needed for complete closure. The primary outcome was complete closure rate, with secondary outcomes including the sustained closure rate at 4 to 5 days post-ESD, closed defect size, closure time, number of additional clips, and incidence of delayed AEs.Results This study included 118 cases. Complete closure was achieved in 96.6% of cases (114/118) with a sustained closure rate of 93.9% (107/114). The median size of the closed mucosal defects was 30 mm (interquartile range [IQR]: 25–38, range: 15–74). The median closure time was 14 minutes (IQR: 11.25–17), and the median number of additional clips deployed was six (IQR: 4–7). Stenosis requiring balloon dilatation was observed in one patient; however, there were no instances of post-ESD bleeding or delayed perforation.Conclusions The Loop9 method proved feasible and effective for closing mucosal defects following colorectal ESD, achieving high rates of complete and sustained closure.
Keywords: Endoscopy Lower GI Tract; Colorectal cancer; Endoscopic resection (polypectomy, ESD, EMRc, ...); Quality and logistical aspects; Performance and complications; Polyps / adenomas / ...